Penerapan Good Governance dalam Perspektif Transparansi dan Akuntabilitas terhadap Efektivitas Program E-auction di Kantor Pelayanan Kekayaan Negara dan Lelang Jakarta II - Zikra, Syarifatuz; Cadith, Juliannes; Wicaksono, Agung Satrio (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The e-auction program was introduced to promote transparency and accountability; however, it continues to face challenges, including technical disruptions, slow document verification, and negative public perceptions. This study examines the influence of good governance—specifically the principles of transparency and accountability—on the effectiveness of the e-auction program at the State Assets and Auction Service Office (KPKNL) Jakarta II. Using a quantitative approach, data were collected through questionnaires and analyzed using multiple linear regression. The study involved 100 purposively selected respondents who had participated in e-auctions at KPKNL Jakarta II. The findings reveal that both transparency and accountability have a positive and significant impact on the program'seffectiveness. These results suggest that strengthening these principles can enhance the efficiency and reach of the e-auction system. This study offers practical recommendations for KPKNL to improve the implementation of e-auctions in a more transparent, accountable, and inclusive manner.